Standardization of Nursery Techniques of Acacia auriculiformis A. Cunn Ex Benth under North Indian Moist Climatic Conditions : Art I Method of Seed Sowing and Irrigation Schedule - Bahuguna, V. K.; Lal, Pyare (Indian Forester, 1992)
Acacia auriculiformis a native of North Australia is frequently planted in various parts of India. The paper presents the results of nursery trials conducted by the Silviculture Division of Forest Research Institute, Dehra Dun to find out the best combinations of seed sowing and irrigation schedule. The results showed that dibbling method of sowing with twice a day irrigation gave good results.